Focus Group Discussion Pendidikan Wirakoperasi Mahasiswa Indonesia - Agus Eko Sujianto; Adimas Agus Ahmad Asy'arie; Mei Santi; Peni Haryanti; Mirza Avicenna Asyifyan; Abdul Rokhim (Pusat Riset dan Inovasi Nasional, 2025)
The general problem faced by cooperatives is the low quality of Human Resources (SDM) managerial in managing the entities owned by these members. So the specific objective of this community service is directed at constructing the management's understanding of entrepreneurial-based cooperative management which is derived to answer 3 (three) specific problems, namely: (1) what is meant by cooperative entrepreneurship towards prosperous members?; (2) why is cooperative entrepreneurship important for student cooperative managers towards prosperous members? and (3) how to internalize cooperative entrepreneurship in student cooperative managers towards prosperous members? The method used is Focus Group Discussion (FGD) with participants being the management of the Student Cooperative (Kopma) al-Kautsar UIN Sayyid Ali Rahmatullah Tulungagung. The results of the service show that Kopma members have the same insight in perceiving cooperative entrepreneurship, namely the entrepreneurial spirit of members. Entrepreneurial spirit is a member modality shown by the creativity and independence of members. Meanwhile, the strategy to internalize cooperative entrepreneurship is by translating cooperative values ​​reflected in a responsible attitude implemented in the form of an Annual Members Meeting (RAT).